Metode Design Thinking Perancangan User Interface dan User Experience Aplikasi “KuyBaca” - Imanda , Ragil Tegar; Mukhayaroh , Anna (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
This research proposes a design thinking style in design that can be applied gradually and is easy to understand, so that visual works can be accurately implemented in any medium. By understanding the design thinking method, designers will have a better understanding of the characteristics and process of creation, so that the creation of works has higher quality, innovation, and objectivity and can be accepted by a large audience. The result of this research is a reading application display on Android-based smartphones that presents in the form of text, images, and sound elements. In this application, there are also novels, poems, and the latest news that are updated every day. This research discusses problem analysis, system requirements analysis, manual data analysis, and decision support system design using design thinking method for UI/UX design on KuyBaca application. After the design process and testing of respondents, it was found that the application design made it easier for users to carry out activities in the application. The effectiveness of UI/UX in the KuyBaca application can be proven from the results of testing the design. Users can understand the flow of the application and can carry out their duties.